The level of IL-12, IL-10, IL-4, and MMP-13 in cutaneous leishmaniasis patients - Abrar Kareem Dhari; Ali Mohammed Abed; Suha Maher Abed (Medical Journal of Babylon)
Background: Cutaneous leishmaniasis (CL) is a dermatological condition that arises due to the presence of protozoan parasites. The disease disproportionately impacts those residing in economically disadvantaged regions and is closely linked to factors such as inadequate nutrition, population displacement, substandard living conditions, and compromised immune systems. Objectives: Investigating the most important immunological changes associated with infection in patients with CL by measuring the levels of some cellular kinetics interleukins-12 (IL-12), IL-10, IL-4, and human matrix metalloproteinase-13 (MMP-13). Materials and Methods: This study involved a sample that included 90 individuals, comprising 20 control subjects and 70 patients diagnosed with CL. The age distribution of the participants in the study spanned from 3 months to 65 years, encompassing individuals of both genders. The sample consisted of 50 females and 40 males. The amounts of IL-12, IL-10, IL-4, and MMP-13 were quantified via an enzyme-linked immunosorbent assay (ELISA) test. Results: The current study showed a significant increase in the level of IL-12 in patients with CL (461.5 ± 14.8) compared to the control group (321.6 ± 57.9) at probability 0.05, whereas non-significant differences in levels of IL-10 and MMP-13 in patients with CL (143.5 ± 6.8) (5.7 ± 0.2) compared with the control group (198.0 ± 35.2) (6.9 ± 0.6) at P ≤ 0.05, respectively. As well as a highly significant decrease in the level of IL-4 in patients with CL (15.5 ± 1.5) compared to the control group (46.3 ± 5.7) at P ≤ 0.05. Conclusion: There was an increasing serum of IL-12 and decreased IL-4 in patients with CL compared with control, while non-significant decreases in the level of MMP-13 and IL-10 between patients with CL and control.